2020
DOI: 10.1186/s13660-020-2309-y
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of λ-Bernstein operators based on (p, q)-integers

Abstract: In the present paper, we construct a new class of positive linear λ-Bernstein operators based on (p, q)-integers. We obtain a Korovkin type approximation theorem, study the rate of convergence of these operators by using the conception of K-functional and moduli of continuity, and also give a convergence theorem for the Lipschitz continuous functions. MSC: 41A10; 41A25; 41A36

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Proof. We get Equation (9) easily by Equations (5) and (6) and [23]. From Equations (5), (7), (8) and…”
Section: Some Preliminary Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proof. We get Equation (9) easily by Equations (5) and (6) and [23]. From Equations (5), (7), (8) and…”
Section: Some Preliminary Resultsmentioning
confidence: 99%
“…Therefore, Equations (11) and (12) can be obtained by Equations (12), (14), [23] and some tedious computations, here we omit those processes.…”
Section: Some Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there was no significant difference in the absolute values of these enzymes. Furthermore, another study 6 reported that 10% and 6% of patients had increased levels of ALT and AST (more than 3 × ULN) during hospitalization, respectively. More importantly, the multivariable logistic regression showed elevated liver test values (≥3 × ULN) during hospitalization were independent predictors of severe illness.…”
mentioning
confidence: 98%
“…For example, COVID-19 patients are more likely to have abnormalities in GGT levels than that of ALP. 4 , 6 Thus, we think it is necessary to take GGT into consideration while evaluating COVID-19-related liver function. We agree with Ye’s proposal 3 that international consensus on the definition of COVID-19-associated liver injury is needed.…”
mentioning
confidence: 99%